Opioid-Sparring and Multimodal Analgesia as Parts of Enhanced Recovery After Surgery (ERAS) Applied In The Ksatria Airlangga Floating Hospital - Pratama Ananda; Bambang Pujo Semedi; Christrijogo Sumartono Waloejo; Arie Utariani (Indonesian Journal of Anesthesiology and Reanimation, 2021)
Introduction: Enhanced Recovery After Surgery (ERAS) protocol is a perioperative multimodal service program designed to achieve a faster surgical recovery period and a better outcome, the key in reducing morbidity in surgery is by reducing the "surgical injury” and reducing the body's stress response caused by the surgery. The success of the ERAS protocol depends on the interpretation and collaboration of the multidisciplinary team, therefore though the protocol is carried out in a hospital that has sufficient facilities and resources, the obstacle in the implementation of ERAS can still happen. The implementation of ERAS protocol in the non-permanent hospital service facility becomes a challenge in itself. Case Reports: From the two case reports of the implementation of ERAS protocol in the Ksatria Airlangga Floating Hospital (RST-KA) it is obtained that the key success of the anesthesia in ERAS protocol above lies on the administration of opioid-sparring therapy where it will reduce the use of opioid. Although there are many obstacles obtained in the RST-KA, the use of ERAS protocol can be conducted by making effective use of opioid-sparring combined with the administration of multimodal analgesia. Conclusion: Therefore, it can be concluded that the ERAS protocol can be applied in the social service concept in the non-permanent health facility.